The Implementation of Administrative Sanctions Against Environmental Violations Committed by Mining Companies in West Nusa Tenggara Province - Jayadi, Muhammad Irfan; Hidayat, Ilham (Justicia Insight, 2025)
Environmental law enforcement plays a crucial role in preserving ecological sustainability, particularly in regions with intensive mining activities such as West Nusa Tenggara Province (NTB), Indonesia. This study aims to analyze the implementation of administrative sanctions against mining companies that violate environmental regulations and to evaluate the effectiveness of these sanctions based on existing legal frameworks, particularly Law No. 32 of 2009 on Environmental Protection and Management. The research adopts an empirical juridical approach, utilizing document analysis and interviews with officials from the NTB Provincial Environmental Agency and affected community members. The findings reveal that although the normative legal framework for administrative sanctions is well established, its implementation faces numerous challenges, including weak supervision, limited human resources, and the influence of economic and political interests. Furthermore, discrepancies between the severity of violations and the types of sanctions imposed reduce the deterrent effect on offenders. Therefore, strengthening institutional capacity and ensuring transparency in environmental law enforcement are essential to uphold ecological justice and protect the public's right to a healthy environment.